Empirical assessment of functional somatic disorder (FSD): frequency, applicability, and diagnostic refinement in a population-based sample - Abigail Smakowski; Judith Rosmalen; Bernd Löwe; Christopher Burton; Anne Toussaint (BMC Medicine)
Abstract Background Persistent and troublesome physical symptoms are common and can, regardless of their cause, greatly impair patients’ quality of life. Reflecting complex brain-body interactions, they are observed across all healthcare specialties, commonly overlap across them, and receive inconsistent diagnoses. In response, the international research network EURONET-SOMA has proposed a diagnostic classification for persistent and troublesome symptoms entitled “functional somatic disorder (FSD)”. Focusing on symptom patterns across organ systems, the FSD approach aims to enhance diagnosis, treatment, and healthcare access for patients. However, further research is needed to validate its effectiveness and clinical utility. This study assessed the frequency and applicability of the FSD proposal within a population-based sample. Methods FSD diagnostic criteria were cross-sectionally operationalised within the multi-disciplinary prospective cohort study Lifelines, conducted in the Dutch population. Kruskal–Wallis and chi-square tests with effect size estimates were used to investigate differences in the diagnostic subgroups regarding chronic diseases, functional comorbidities and psycho-behavioural features. Binary logistic regression with elastic net penalisation was used to investigate sociodemographic, psycho-behavioural and clinical factors associated with FSD. Results Of the study population (N = 88,925), 58% met the diagnostic criteria for FSD. Of those meeting FSD, 31% reported a single distressing symptom, 18% had several symptoms attributable to one organ system and 52% reported multiple symptoms from various organ systems. Moderate differences between these subgroups were found for health status, neuroticism, long-term life difficulties and healthcare utilisation. Elastic net regression showed comorbid chronic musculoskeletal (OR 1.8), gastrointestinal disease (OR 1.4), neurological disease (OR 1.2), and female sex (OR 1.2) predicted FSD. Concurrent anxiety (OR 1.6), healthcare visits (OR 1.3) and long-term difficulties (OR 1.2) were associated with the presence of FSD. Conclusions This study supports refining the FSD criteria to avoid over-inclusiveness. Current symptom severity and frequency thresholds need adjustment to better identify those needing treatment. The distinction between single and multiple symptom categories is important, and optional specifiers like comorbid chronic diagnoses and psychological factors seem valuable for predicting FSD. Despite warranting further research, the FSD classification is promising for diagnosing persistent and troublesome symptoms across medical specialties.